#### Answer

$= (-\frac{1}{3})^{2}+(\frac{1}{4})(-\frac{4}{9}) = 0$

#### Work Step by Step

$= (-\frac{1}{3})^{2}+(\frac{1}{4})(-\frac{4}{9})$
$= (\frac{1}{9})-(\frac{4}{36})$
$= (\frac{1}{9}) - (\frac{1}{9})$
$=0$

Published by
Pearson

ISBN 10:
0321825535

ISBN 13:
978-0-32182-553-7

$= (-\frac{1}{3})^{2}+(\frac{1}{4})(-\frac{4}{9}) = 0$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.